Masculinities and respect in the group context of gangs - Hughes, Lorine A. (The Oxford handbook of gangs and society, 2024)
This chapter delineates the history and significance of masculinities within the gang literature. Following the second women’s movement, crime and violence came to be understood as means by which male and female offenders, including gang members, accomplish gender. While criminological debates over the nature and behavioral effects of feminine gender identities remain unresolved, masculinities frequently are implicated in explanations of gang crime and violence, particularly as related to street codes, street culture, and street socialization. This body of work conceptualizes masculinity as a resource for obtaining respect and shows how it is accomplished through violence and other public displays of toughness. Missing from this literature, which focuses primarily on individual action and macro-level considerations, is attention to complementary micro-level group dynamics in which enactments of masculinity unfold. After discussing the role of group structure and process in transforming performances of masculinity, including violence, into contextual resources for earning and maintaining respect, the chapter concludes with recommendations for future research.